What Do You Want Us to Know?: Learning From Life Stories to Improve Veterans' Healthcare Experiences. (January 2022) - Rosen, Miriam; Nguyen, Breanna A.; Khetarpal, Susheel; Sgro, Gaetan
My Life My Story (MLMS) is a national Veterans Health Administration (VA) life story interview program that aims to provide more humanistic care for veterans by focusing on the patient as a person. Our project took place at the Pittsburgh VA Healthcare System and had 3 main goals: (1) describe themes that emerge in MLMS interviews from the prompting question, what do you want your healthcare provider to know about you? ; (2) identify topics of importance to veterans and suggest ways for healthcare providers to explore them; and (3) foster a culture at the Pittsburgh VA that places not only the health but also the personal triumphs, hardships, and aspirations of veterans at the center. Veterans provided verbal consent to have their previously recorded stories used in this study. Stories were coded and then analyzed for patterns and themes. A total of 17 veterans participated in our study. Themes that emerged from the stories include (1) Early Hardships; (2) Economic Disadvantage; (3) Polaroid Snapshots; (4) Around the World; (5) Haunted by Combat; (6) Life-altering Moments; (7) Homecoming; (8) Romantic Beginnings & Obstacles; (9) Inequity across Gender & Race; and (10) Facing Mortality. This study's findings underscore the need to address the traumas associated with military service, as well as the challenges faced with re-integration into civilian life, when working with veterans. The MLMS interviews explored in this study can help clinicians identify topics of importance to veterans, strengthen their relationships with their patients, and improve the care that veterans receive.